Кинетика усадки при спекании сплавов Сu-Ni, Cu-Fe и Ni-Fe с последующим прессованием - Бондаренко, Н.А.; Мечник, В.А.; Лошак, М.Г.; Супрун, М.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
It is studied shrinkage kinetics at sintering of binary systems Cu-Ni, Fe-Cu and Fe-Ni in a usual muffle furnace with the subsequent pressing. It is shown, that the increase in pressure of pressing promotes active diffusion and to chemical processes at hot pressing. It positively tells on structure and properties of ready samples.